Rancang Bangun Kendali Pakan Ikan Lele Jarak Jauh Berbasis Internet of Things (IoT) di UMKM Peternakan Ikan Lele Ciomas - Annas Rifai; Hartanto S Nugraha; Daffa Aury Bastian Assa; Istiqomatun Nisaa (Institut Nalanda, 2026)
One of the main problems in catfish farming is that feed costs account for up to 70% of total expenses. Feeding is often uncontrolled—for example, when employees are sick, on sick leave, or on holiday. This can result in catfish deaths. In addition, delays or irregularities in the feeding schedule can affect the growth and productivity of catfish. In this paper, this problem is addressed through the use of IoT technology. IoT enables remote control of catfish feeding using a microcontroller, an Internet shield, and servo motors. The developed system is designed to help catfish farmers manage feeding in a more regular and scheduled manner. The results of this study include a catfish feeding device and a website that can be used to control catfish feeding remotely. The feeding device is integrated with the website, which can regulate the amount and timing of feed to be provided to the catfish. Test results show that this IoT-based feeding system makes the amount and timing of feed distribution more efficient, thereby helping to improve the effectiveness of catfish farming management and reduce the risk of errors in the feeding process.